2023
DOI: 10.3390/antibiotics12121693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Healthcare-Associated Infections in Public Hospitals: A Cross-Sectional Study

Daniela Iancu,
Iuliu Moldovan,
Brîndușa Țilea
et al.

Abstract: Background: Hospital-acquired infections (HAIs) pose a significant danger to global public health, mainly because their numbers are growing exponentially each year. Additionally, the rise of bacterial strains resistant to current treatment options further exacerbates this threat. This study aimed to examine the occurrences of HAIs identified in public hospitals at the county level. Methods: We conducted a cross-sectional study utilizing data provided to the Mures Public Health Directorate from all the public h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…K. pneumoniae is a Gram-negative bacterium that can cause bacteremia, sepsis, hospital-acquired urinary tract infections, pneumonia and nosocomial infections . Studies have shown that K.…”
mentioning
confidence: 99%
“…K. pneumoniae is a Gram-negative bacterium that can cause bacteremia, sepsis, hospital-acquired urinary tract infections, pneumonia and nosocomial infections . Studies have shown that K.…”
mentioning
confidence: 99%